2020
DOI: 10.1101/2020.04.08.20056929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introductions and early spread of SARS-CoV-2 in the New York City area

Abstract: New York City (NYC) has emerged as one of the epicenters of the current SARS-CoV2 pandemic. To identify the early events underlying the rapid spread of the virus in the NYC metropolitan area, we sequenced the virus causing COVID19 in patients seeking care at the Mount Sinai Health System. Phylogenetic analysis of 84 distinct SARS-CoV2 genomes indicates multiple, independent but isolated introductions mainly from Europe and other parts of the United States. Moreover, we find evidence for community transmission … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 18 publications
4
27
1
Order By: Relevance
“…The diversity present in our 320 viral genomes contrasts somewhat with data reported recently by Gonzalez-Reiche et al (30), who studied 84 SARS-CoV-2 isolates causing disease in patients in the New York City region. Those investigators concluded that the vast majority of disease was caused by progeny was not certified by peer review) is the author/funder.…”
Section: Discussioncontrasting
confidence: 96%
“…The diversity present in our 320 viral genomes contrasts somewhat with data reported recently by Gonzalez-Reiche et al (30), who studied 84 SARS-CoV-2 isolates causing disease in patients in the New York City region. Those investigators concluded that the vast majority of disease was caused by progeny was not certified by peer review) is the author/funder.…”
Section: Discussioncontrasting
confidence: 96%
“…According to air transport statistics from the World Bank (https://data.worldbank.org) and the National Government We estimated these introductions could have occurred as early as mid-February, around 1 month before first cases were reported in Uruguay in March 13 th . This is in line with observations from other geographic regions, for example, in New York first cases were confirmed in March but a recent study suggested that initial virus introductions could be traced back to February 20 th [10]. Also, the virus was likely introduced in Europe by a traveler that arrived from Wuhan to France, but the recent identification of a group of ill Chinese tourists in France previous to this case supports earlier introductions [11].…”
Section: Discussionsupporting
confidence: 90%
“…Retrospective analysis could illuminate the degree of undetected community spreading on a per-region basis, to assess the efficacy of policy and behavioral changes, and prospectively to inform proactive management of an ongoing outbreak 15 . Two other groups have reported sequencing surveillance of nearby or overlapping regions 16,17 , and monitoring of a hospital system could be complemented by broader population studies 18 . Given the logistical and regulatory hurdles to establishing such surveillance, it is critical to have this infrastructure already in place for future waves of COVID-19 or other future pandemics.…”
Section: Discussionmentioning
confidence: 99%